ChemInform Abstract: Click Reaction in Carbohydrate Chemistry: Recent Developments and Future Perspective. Issue 20 (25th April 2013) - Kushwaha, Divya; Dwivedi, Pratibha; Kuanar, Saroj K.; Tiwari, Vinod K.
Abstract Review: 227 refs.